Gastric motility in soluble guanylate cyclase α(1) knock-out mice - Vanneste, Gwen (Blackwell Science Inc, 2007)
The principal target of the relaxant neurotransmitter nitric oxide (NO) is soluble guanylate cyclase (sGC). As the α(1)β(1)-isoform of sGC is the predominant one in the gastrointestinal tract, the aim of this study was to investigate the role of sGC in nitrergic regulation of gastric motility in male and female sGCα(1) knock-out (KO) mice. In circular gastric fundus muscle strips, functional responses and cGMP levels were determined in response to nitrergic and non-nitrergic stimuli. sGC subunit mRNA expression in fundus was measured by real-time RT-PCR; in vivo gastric emptying of a phenol red meal was determined. No changes were observed in sGC subunit mRNA levels between wild-type (WT) and KO tissues. Nitrergic relaxations induced by short trains of electrical field stimulation (EFS) were abolished, while those by long trains of EFS were reduced in KO strips; the latter responses were abolished by 1H[1,2,4,]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ). The relaxations evoked by exogenous NO and the NO-independent sGC activator BAY 41-2272 were reduced in KO strips but still sensitive to ODQ. Relaxations induced by vasoactive intestinal peptide (VIP) and 8-bromo-cGMP were not influenced. Basal cGMP levels were decreased in KO strips but NO, long train EFS and BAY 41-2272 still induced a moderate ODQ-sensitive increase in cGMP levels. Gastric emptying, measured at 15 and 60 min, was increased at 15 min in male KO mice. sGCα(1)β(1) plays an important role in gastric nitrergic relaxation in vitro, but some degree of nitrergic relaxation can occur via sGCα(2)β(1) activation in sGCα(1) KO mice, which contributes to the moderate in vivo consequence on gastric emptying.